Multi-environment evaluation of oil accumulation pattern parameters in olive - Navas López, José F. (2019)
The pattern of olive oil accumulation is of paramount importance in olive because its influence in determining final oil yield and optimal harvesting date. In this work, we have evaluated the genetic and environment influence on the olive oil accumulation pattern. For that purpose, a set of cultivars and breeding selections planted in a multi-environment trial was evaluated in two consecutive harvest seasons. Significant effect of the environment, genotype and their interaction were observed for the maximum oil content reached and the rate of oil accumulation. On the contrary, the date of maximum oil content seems to depend only on the environment. The two breeding selections evaluated showed, in general, high stability and adaptability in oil accumulation parameters. Among the potential environmental factors that could affect oil accumulation, PLS analysis suggests that temperature could play a determinant environmental effect in the oil accumulation parameters tested in this study. These results underline the relevance of using multi-environment trials for adequate characterization of genotypes showing either good behaviour in variable environments or only under specific environmental conditions.